2000
DOI: 10.1063/1.372052
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet electroluminescence in GaN/AlGaN single-heterojunction light-emitting diodes grown on Si(111)

Abstract: GaN:Mg/AlGaN single-heterojunction light-emitting diodes were grown on Si(111) substrates by plasma-assisted molecular-beam epitaxy. High-quality Mg-doped GaN layers with hole concentrations up to 1.2×1017 holes/cm3 and intense low-temperature photoluminescence, which increases in annealed samples, were obtained. Smooth AlGaN layers, with surface roughness below 5 nm, were used as buffer layers. Continuous-wave room-temperature ultraviolet electroluminescence was observed at 365 nm with a full width at half ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…AlN is frequently used as a buffer layer for molecular beam epitaxy deposition of III-nitride thin films on Si [6,7,[13][14][15][16]. It might be expected that this might have a deleterious effect on transport as AlN would be expected to be an insulator.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AlN is frequently used as a buffer layer for molecular beam epitaxy deposition of III-nitride thin films on Si [6,7,[13][14][15][16]. It might be expected that this might have a deleterious effect on transport as AlN would be expected to be an insulator.…”
Section: Introductionmentioning
confidence: 99%
“…Growth of In x Ga 1-x N-based opto-electronic device structures on Si has been extensively investigated previously with the goal of optimizing the interface layer(s) between the Si and the active layers to reduce defects in the nitride layers and to improve device performance [6]. Light emitting diode structures have been fabricated either using standard top and mesa electrical contacts to the nitride layers [7] or using n-Si as the back contact [8][9][10]. In this latter case, electrical transport between the Si substrate and the epilayer is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…These phenomena indicate that the band-edge emission from the MQWs becomes dominant at higher forward currents. Previous investigators have reported that either the intensity of the shorter wavelength peak is saturated or this peak shifts to a longer wavelength as a function of increasing injection current due to heating of the device [1][2][3][4]. However, neither a saturation in the intensity nor a shift in the position of the 353 nm peak was observed, even when the dc injection current was increased to 200 mA (∼200 A/cm 2 ), as shown in Fig.…”
Section: Ohmic Contacts To N-type Sicmentioning
confidence: 43%
“…However, the light output power of these devices has been reported [1][2][3][4] to be much lower than that obtained from InGaN-based visible LEDs.…”
Section: Introductionmentioning
confidence: 85%
“…Bottom right: intensity profiles for the n-GaN, p-GaN, and InGaN luminescence compared to samples grown on silicon, and even comparable to samples grown on sapphire by other groups [10,11,[20][21][22][23]. Optimizing the diode shape to improve the light outcoupling is likely to reduce losses and enhance the LED efficiency significantly.…”
Section: Resultsmentioning
confidence: 99%